INNOVATION PROJECTS AS A FACTOR FOR STRATEGIC DEVELOPMENT OF SMALL AND MEDIUM - SIZED ENTERPRISES - Filipova, Milena; Yuleva-Chuchulayna, Radostina (Revista Inclusiones, 2020)
Innovative projects are aimed at creating new products under the influence of new searches and trends in society. Small and medium-sized (SME’s) enterprises aim to develop and implement such an innovation project, which will help the strategic development of the organization and the achievement of higher competitiveness. In the modern dynamic market and strong competition, they manage to develop and exist those companies that implement innovations or constantly improve their products. Innovation is the foundation of small and medium business growth. It is for this reason that it is important that the managers establish such an innovative plan to develop the company, even if it happens through partnership with other businesses. The main objectives of this development are to systematize the essence of the concepts of "innovation", "Innovative activity", "strategic development", "innovation plan", as well as clarifying the relationship between innovation planning and strategic development of Small and medium-sized enterprises. It has also clarified the consistency in the development of innovative projects. Systemized are the characteristic features that it possesses. The main tasks of the innovative projects and the advantages they give in implementing them are listed. For the purpose of the research, the thematic-problematic sections of innovative projects are identified. The main research methods used in the development are content analysis, method of analysis and synthesis, intuitive and systematic approach.